Antimicrobial resistance in pathogenic aerobic bacteria causing surgical site infections in Mbarara regional referral hospital, Southwestern Uganda - Hope, Derick; Ampaire, Lucas; Oyet, Caesar; Muwanguzi, Enoch; Twizerimana, Hillary; Apecu, Richard Onyuthi (Scientific reports, 2019)
Surgical site infections (SSI) remain a common postoperative complication despite use of prophylactic antibiotics and other preventive measures, mainly due to increasing antimicrobial resistance. Here, we present antimicrobial resistance rate of bacteria isolated in clinical cases of SSI. A hospital based descriptive cross sectional study was conducted on 83 consented postoperative patients with clinical SSI. Data on patients was obtained using structured data collection form. Two swabs were collected aseptically from each patient. Bacteriological culture examination and identification was done following standard microbiological techniques. Antibiotic susceptibility test was done by Kirby-Bauer disc diffusion method. Gram negative bacteria (GNB) were predominant (65.59%) with the dominant being Klebsiella species (29.03%). Overall 86% of aerobic bacteria isolated were multidrug resistant (MDR) where 65.63% and 96.72% of Gram positive and Gram negative isolates were MDR respectively. All the isolates with exception of Enterococci species were resistant to ampicillin. GNB showed high resistance to ceftriaxone, sulfamethoxazole/trimethoprim and gentamicin. All the isolated Klebsiella spp were MDR. S. aureus were all resistant to oxacillin. The isolation rate was higher in emergency, males and dirty wounds in relation to nature of surgery, gender and class of surgical wound respectively. These findings necessitate judicious antibiotic use and calls for surveillance of SSIs periodically as well as strict adherence to good sanitation practice to reduce spread of drug-resistant pathogens
Keywords: Antimicrobial resistance; Pathogenic aerobic bacteria; Surgical site infections; Uganda; Postoperative complication